2009
DOI: 10.1002/zaac.200800361
|View full text |Cite
|
Sign up to set email alerts
|

Rare‐Earth‐Rich Magnesium Compounds RE23Rh7Mg4 (RE = La, Ce, Pr, Nd, Sm, Gd) with Tetrahedral Mg4 Clusters

Abstract: The rare earth‐rich compounds RE23Rh7Mg4 (RE = La, Ce, Pr, Nd, Sm, Gd) were prepared by induction‐melting the elements in sealed tantalum tubes. The new compounds were characterized by X‐ray powder diffraction. They crystallize with the hexagonal Pr23Ir7Mg4 type structure, space group P63mc. The structures of La23Rh7Mg4 (a = 1019.1(1), c = 2303.7(4) pm, wR2 = 0.0827, 1979 F2 values, 69 variables), Nd23Rh7Mg4 (a = 995.4(2), c = 2242.3(5) pm, wR2 = 0.0592, 2555 F2 values, 74 variables) and Gd23Rh6.86(5)Mg4 (a = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Careful evaluation of the data sets then showed that the systematic extinctions were compatible with space group P6 3 mc, in agreement with the Pr 23 Ir 7 Mg 4 type [10]. The atomic parameters of isotypic La 23 Rh 7 Mg 4 [12] were taken as starting values, and the three structures were refined using SHELXL-97 [23] (full-matrix least-squares on F 2 ) with anisotropic atomic displacement parameters for the rare earth and transition metal atoms and isotropic displacement parameters for the light magnesium atoms. Since the structure refinement of the prototype Pr 23 Ir 7 Mg 4 [10] revealed small defects on the Ir2 site, also the occupancy parameters of the RE 23 Ru 7 Mg 4 crystals were refined in separate series of leastsquares cycles.…”
Section: Structure Refinementsmentioning
confidence: 92%
See 1 more Smart Citation
“…Careful evaluation of the data sets then showed that the systematic extinctions were compatible with space group P6 3 mc, in agreement with the Pr 23 Ir 7 Mg 4 type [10]. The atomic parameters of isotypic La 23 Rh 7 Mg 4 [12] were taken as starting values, and the three structures were refined using SHELXL-97 [23] (full-matrix least-squares on F 2 ) with anisotropic atomic displacement parameters for the rare earth and transition metal atoms and isotropic displacement parameters for the light magnesium atoms. Since the structure refinement of the prototype Pr 23 Ir 7 Mg 4 [10] revealed small defects on the Ir2 site, also the occupancy parameters of the RE 23 Ru 7 Mg 4 crystals were refined in separate series of leastsquares cycles.…”
Section: Structure Refinementsmentioning
confidence: 92%
“…F43m) and hexagonal for the Pr 23 Ir 7 Mg 4 type (space group P6 3 mc). Cavities within these networks are filled by tetrahedral Mg 4 clusters, a rare structural motif in magnesium chemistry [12]. First investigations revealed interesting properties for these rare earth-rich materials.…”
Section: Introductionmentioning
confidence: 99%
“…An assignment of the Pr 23 Ir 7 Mg 4 -type structure would seem to be evident given its overwhelming pervasiveness compared to the Yb 23 Cu 7 Mg 4 -type structure (Table ). Or is it?…”
Section: Resultsmentioning
confidence: 99%
“…According to literature data, all atomic positions are fully occupied in the structure of Yb 23 Cu 7 Mg 4 as well as in most Pr 23 Ir 7 Mg 4 -type compounds. Some deficient occupancies of transition-metal sites were reported for the structure of Pr 23 Ir 7 Mg 4 itself (Pr 23 Ir 6.81 Mg 4 ), Gd 23 Rh 6.86 Mg 4 , and La 23 Ru 6.87 Cd 4 . The largest homogeneity regions were found for Ce 23 Ru 7+ x Al 4– x (0 < x < 2.97) and Ce 23+ y Ru 7+ x Ga 4– x – y (0 < x < 3.00, 0 < y < 0.97) .…”
Section: Resultsmentioning
confidence: 99%
“…The three structures were refined using SHELXL-97 [11] (full-matrix least-squares on F 2 ) with anisotropic atomic displacement parameters for all atoms. Since the structures of Pr 23 Ir 6.81 Mg 4 [5] and Gd 23 Rh 6.86 Mg 4 [7] showed small defects on the T 2 sites, the occupancy parameters for all three crystals were refined in separate series of least-squares cycles. …”
Section: X-ray Diffractionmentioning
confidence: 99%